Structure Characterization of Materials by Association of the Raman Spectra and X-Ray Diffraction Data - Chagas, Luciano H.; Souza, Márcia C. De; Carmo, Weberton R. Do; Abreu, Heitor A. De; Diniz, Renata (IntechOpen, 2012)
None